Expert System Application for Early Warning Detection of Preeclampsia Risk in the Third Trimester of Pregnancy Using the Forward Chaining Method - Kamiati, Kamiati; Fadly Umar; Silvah, Silvah; Andi Kartiani; Dewi Lestari; Dela Safitri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
During pregnancy there will be changes in the body both physiologically and psychologically. The body's systems will coordinate with each other to maintain pregnancy and give signals to the body that result in discomfort. The creation of this expert system application program is intended to try out an early warning detection plan for the risk of preeclampsia in pregnancy. The method used by forward chaining in research consists of collecting data and information, processing data and information, designing, implementing, testing and evaluating. Conclusion results from the expert system diagnosis process. By creating and designing this expert system, it is hoped that it can increase pregnant women's knowledge about early warning of the risk of preeclampsia in the third trimester of pregnancy independently, quickly and accurately.